2022
DOI: 10.1039/d1ma00831e
|View full text |Cite
|
Sign up to set email alerts
|

Superchiral hot-spots in “real” chiral plasmonic structures

Abstract: Light scattering from chiral plasmonic structures can create near fields with an asymmetry greater than the equivalent circularly polarised light, a property sometimes referred to as superchirality.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…In addition, we observed that the local helicity of the NR surface often changes sign within the same particle. Local helicity could couple to strong local plasmonic fields at sharp corners and edges, leading to a possible dominance of local chiral features in the chiroptical response . Although the simulation results in Figure c question whether this is really the case, they cannot exclude that a local plasmonic effect occurs for highly asymmetric particles with sharp local features as the presented NRs.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, we observed that the local helicity of the NR surface often changes sign within the same particle. Local helicity could couple to strong local plasmonic fields at sharp corners and edges, leading to a possible dominance of local chiral features in the chiroptical response . Although the simulation results in Figure c question whether this is really the case, they cannot exclude that a local plasmonic effect occurs for highly asymmetric particles with sharp local features as the presented NRs.…”
Section: Resultsmentioning
confidence: 88%
“…These measurements revealed that anisotropies and asymmetries, for example, in surface facets distributions, can cause “accidental” geometrical chiral features and might be responsible for the unexpected chiroptical responses. In combination with possible electromagnetic enhancements of local chiral features, these geometrical features can result in strong, although not controllable, g -factors . We can conclude that there is still a lot to be learned about the origin of chiroptical activity in plasmonic systems and showed that single NP correlative measurements are an important tool to do so.…”
Section: Discussionmentioning
confidence: 94%
“…The CPL-active chiral nanostructures were fabricated via template-induced self-assembly of halide perovskite NC inks using three different pre-patterned poly(dimethylsiloxane) (PDMS) molds with 500 nm gammadion-like structures (9 mm 2 patterned areas) with left (L), right (R), and racemic (O) orientations in a square array with a periodicity of 600 nm (structure dimensions in Figure 1c). The gammadion geometry was chosen mainly due to the abundance of previous literature, [28][29][30]32,[41][42][43][44][45][46] which facilitates the comparison between the optical properties of the newly produced nanostructures by nanoimprinting lithography and previous results from structures produced by electronic lithography. Second, the C4 symmetry of the array helps minimizing the contribution to the PL from linearly polarized light which results in elliptical polarization.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the development of nanotechnology, we can nowadays artificially design novel materials, which exhibit high CD signals. Led by the exotic features of materials at the nanoscale, photonics community has, in fact, proposed plasmonic, dielectric, and hybrid nanostructures with high intrinsic chirality in the visible range. Recent experimental studies prove that dielectric and plasmonic periodically arranged nanostructures can improve chiral sensing of specific enantiomers. , Moreover, even if the nanostructure is not intrinsically chiral, the symmetry of the light–matter interaction can be broken with an experimental setup .…”
Section: Introductionmentioning
confidence: 99%